Enhancing visual communication through representation learning - Wei, YuHan; Lee, ChangWook; Han, SeokWon; Kim, Anna (Frontiers in Neuroscience, 2024)
Introduction This research aims to address the challenges in model construction for the Extended Mind for the Design of the Human Environment. Specifically, we employ the ResNet-50, LSTM, and Object Tracking Algorithms approaches to achieve collaborative construction of high-quality virtual assets, image optimization, and intelligent agents, providing users with a virtual universe experience in the context of visual communication. Methods Firstly, we utilize ResNet-50 as a convolutional neural network model for generating virtual assets, including objects, characters, and environments. By training and fine-tuning ResNet-50, we can generate virtual elements with high realism and rich diversity. Next, we use LSTM (Long Short-Term Memory) for image processing and analysis of the generated virtual assets. LSTM can capture contextual information in image sequences and extract/improve the details and appearance of the images. By applying LSTM, we further enhance the quality and realism of the generated virtual assets. Finally, we adopt Object Tracking Algorithms to track and analyze the movement and behavior of virtual entities within the virtual environment. Object Tracking Algorithms enable us to accurately track the positions and trajectories of objects, characters, and other elements, allowing for realistic interactions and dynamic responses. Results and discussion By integrating the technologies of ResNet-50, LSTM, and Object Tracking Algorithms, we can generate realistic virtual assets, optimize image details, track and analyze virtual entities, and train intelligent agents, providing users with a more immersive and interactive visual communication-driven metaverse experience. These innovative solutions have important applications in the Extended Mind for the Design of the Human Environment, enabling the creation of more realistic and interactive virtual worlds.